Worker Stress, Burnout, and Wellbeing Before and During the COVID-19 Restrictions in the United Kingdom - Pelly, Diane; Daly, Michael; Delaney, Liam; Doyle, Orla (Frontiers in Psychology, 2022)
COVID-19 created a transformational shift in the working environment for much of the labour force, yet its impact on workers is unclear. This study uses longitudinal data to examine the well-being of 621 full-time workers assessed before (November 2019 - February 2020) and during (May - June 2020) the first lockdown in the UK. We employ fixed effects analyses to investigate the impact of the restrictions and mandatory homeworking on cognitive, emotional and psychological well-being. Within the sample, the rate of full-time homeworking increased from 2 to 74 percent between waves. We identify significant changes in 9 of the 15 measures assessed, with a general pattern of improvements in well-being during lockdown. Overall levels of stress, self-rated mental health, positive emotions and life and job satisfaction are not adversely affected by the restrictions. There is a reduction in the burnout symptoms of disengagement (-.13 sd) and exhaustion (-.20 sd) and in the frequency with which negative emotions are experienced at work (-.15 sd). Workers feel more autonomous (+.09 sd), closer to their co-workers (+.10 sd) and more attached to their organisations (+.19 sd). However, homelife satisfaction declines (-.11 sd). These findings highlight the possibility that the COVID-19 pandemic and large-scale transition to homeworking was associated with unchanged or improved worker well-being. This study has important implications for governments and employers regarding a global shift to homeworking. JEL codes: J08; J24; I31